Optimalisasi Layanan Kesehatan Mental Bagi Narapidana di Lapas Perempuan Kelas IIA Pekanbaru - Geri Maulana Fahreza; Ali Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Mental health is an important component at every stage of human life, from childhood, adolescence, to adulthood. It is often stated that mental conditions in childhood can affect a person's psychological development into adulthood. Therefore, it is essential for a person to have a healthy mind from an early age. With a healthy mind, an individual can experience various benefits in life, such as: being more capable of coping with stress and life pressures, being physically healthy, establishing good relationships with others, contributing to society, working productively, and being aware of one's potential. Moreover, mental and physical health are closely linked. A person with a mental disorder, particularly depression, can increase the risk of various physical problems in the future, such as strokes, type 2 diabetes, and heart disease. Conversely, chronic physical conditions can also increase the risk of mental disorders in a person. Therefore, maintaining both mental and physical health is crucial to prevent various diseases.